THE EFFECT OF PURPLE SWEET POTATO (IPOMOEA BATATAS) ON ELEVATED HEMOGLOBIN LEVELS IN PREGNANT WOMEN MID AND LATE PREGNANCY IN A WORKING AREA TABIR LINTAS HEALTH CENTER MERANGIN DISTRICT - Donna Harriya Novidha; Zuriah - (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
The occurrence of anemia in Tabir Lintas Health Center from January to August, the cumulative number of pregnant women is 88, with only 51 examined, and 37 pregnant women who have not been tested for hemoglobin. The purpose of this study is to determine the effect of purple sweet potato (Ipomoea Batatas) on increasing hemoglobin levels in pregnant women in the second and third trimester in the working area of Tabir Lintas Health Center in Merangin district in 2023, the study design is a quasi-experimental with one group pretest-posttest design, the total sample size was 20 pregnant women, data collection was done using observation sheets, and data analysis was done using t-tests. According to the study results, the mean hemoglobin levels before administration of purple sweet potato (Ipomoea Batatas) were 8.8 gr/dl at the lowest, 10.4 gr/dl at the highest, 10.6 gr/dl at the lowest and 11.8 gr/dl at the highest. In conclusion of the study results, the effect of purple sweet potato (Ipomoea Batatas) on hemoglobin levels of Trimester II and III pregnant women had a p-value of 0.000 < (0.05). It is hoped that midwives counseling and using purple sweet potato during pregnancy as an alternative means of increasing hemoglobin levels in pregnant women will increase mothers' knowledge and insight in the prevention and treatment of anemia.